2022
DOI: 10.3390/nu14153048
|View full text |Cite
|
Sign up to set email alerts
|

Positive Effects of Vitamin D Supplementation in Patients Hospitalized for COVID-19: A Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: Retrospective studies showed a relationship between vitamin D status and COVID-19 severity and mortality, with an inverse relation between SARS-CoV-2 positivity and circulating calcifediol levels. The objective of this pilot study was to investigate the effect of vitamin D supplementation on the length of hospital stay and clinical improvement in patients with vitamin D deficiency hospitalized with COVID-19. The study was randomized, double blind and placebo controlled. A total of 50 subjects were enrolled and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 48 publications
2
47
0
Order By: Relevance
“…The current use of high doses of vitamin D in COVID-19 patients is not based on solid evidence. Very recently in a randomized controlled trial with 50 subjects hospitalized for COVID-19 with a mean age of 65 years and a baseline 25(OH)D level at 55 nmol/L, 25,000 IU cholecalciferol/day over 4 consecutive days followed by 25,000 IU/week up to 6 weeks reduced the hospitalization duration (4 days vs 8 days) and the need for supplemental oxygen [138].…”
Section: Metabolic Conditions and Treatment With Calcifediol (25-hydr...mentioning
confidence: 99%
“…The current use of high doses of vitamin D in COVID-19 patients is not based on solid evidence. Very recently in a randomized controlled trial with 50 subjects hospitalized for COVID-19 with a mean age of 65 years and a baseline 25(OH)D level at 55 nmol/L, 25,000 IU cholecalciferol/day over 4 consecutive days followed by 25,000 IU/week up to 6 weeks reduced the hospitalization duration (4 days vs 8 days) and the need for supplemental oxygen [138].…”
Section: Metabolic Conditions and Treatment With Calcifediol (25-hydr...mentioning
confidence: 99%
“…Since the completion of the aforementioned meta-analysis, a number of interventional studies evaluating the impact of vitamin D supplementation on COVID-19 outcomes have been published. [18][19][20][21][22][23][24] All but two of the studies 23,24 found benefits to vitamin D supplementation in patients hospitalized with COVID-19. Of note, bolus dosing was used in both studies that found no benefit, and in the Mariani et al study, baseline 25(OH)VitD levels >30 ng/mL.…”
Section: Clinical Trial Datamentioning
confidence: 99%
“…In contrast to the negative study mentioned earlier, it is possible to review one of the latest studies reported in the vdmetadata.com analysis. In that study, De Niet and colleagues (2022) [80] used a double-blind control design in which hospitalized COVID-19 patients were treated early with multiple doses of vitamin D3 (25,000 IU) for up to 6 weeks. Even though calcifediol was not used, each treated patient received 100,000 IU of vitamin D3 in the first four days, followed by six-weeks of weekly maintenance.…”
Section: Positive Studies: Proper Study Designsmentioning
confidence: 99%